Depression, Associated Factors, and Coping Mechanisms among Caregivers of Children with Cancer at Mobile Hospice Mbarara, Uganda: A Cross-Sectional Study - Ninyikiriza Jackline; Tweheyo Otwiine; Jordan Amanyire (SJ Pediatrics and Child Health Africa, 2026)
Background: Caregivers of children with cancer experience substantial psychological, emotional, and socioeconomic challenges that increase their risk of depression. Despite the growing burden of pediatric cancer in Uganda, evidence on the prevalence of depression, its associated factors, and coping mechanisms among caregivers in palliative care settings remains limited. This study assessed the prevalence of depression, factors associated with depression, and coping mechanisms among caregivers of children with cancer attending Mobile Hospice Mbarara, Uganda. Methods: A facility-based cross-sectional study was conducted among 117 caregivers of children with cancer attending Mobile Hospice Mbarara, consecutively recruited and interviewed using a structured questionnaire. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9), with a score of ≥10 indicating depression. Factors associated with depression were identified using modified Poisson regression with robust standard errors, with results presented as crude and adjusted prevalence ratios (CPR/APR) and 95% confidence intervals (CI). Statistical significance was set at p